Risk factors for depression in adolescents - Okońska, Aleksandra; Hakało, Dominika; Ignatiuk-Chilkiewicz, Marta; Kałuska, Joanna; Jelska, Weronika; Kozakiewicz, Julia; Ziemba, Michał; Kiślak, Magdalena (Quality in Sport, 2025)
Introduction: This study aims to analyze the risk factors associated with depression in adolescents, focusing on the interplay between biological, psychological, and social determinants. Materials and methods: A review of chosen literature from PubMed, and Google Scholar was conducted, using key words including "depression", "adolescence", "stress", "mental health". Summary: Depression in adolescents is strongly associated with significant biological changes, including hormonal shifts, and neural maturation. Gender differences are particularly prominent, with girls showing higher prevalence and severity of depressive symptoms due to factors such as hormonal sensitivity to stress, and genetic variance. Family and interpersonal relationships also play a role, as parental depression, low parental warmth, high criticism, and peer rejection increase the risk of depression. Conversely, positive family dynamics and supportive peer relationships act as protective factors. Sleep disturbances were found to have a profound impact on adolescent mental health. Delayed circadian rhythms, and poor sleep hygiene are linked to increased depressive symptoms. Stressful life events emerged as significant environmental risk factors, with maladaptive coping strategies exacerbating vulnerability. The study underscores the critical mediating role of perceived social support in mitigating the effects of stress on mental health. Conclusions: The findings of this study highlight the need for integrated strategies to address adolescent depression. Interventions should include early detection programs, gender-sensitive approaches, and family-based therapies to foster supportive relationships. Given that depression during adolescence often tracks into adulthood and increases the risk of recurrent episodes and suicidality, targeted efforts during this developmental phase are paramount.